2018
DOI: 10.1590/abd1806-4841.20186068
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor as an incriminating agent in vitiligo

Abstract: BackgroundVitiligo is an autoimmune skin disorder in which the loss of melanocytes is mainly attributed to defective autoimmune mechanisms and, lately, there has been more emphasis on autoinflammatory mediators. Among these is the macrophage migration inhibitory factor, which is involved in many autoimmune skin diseases. However, little is known about the contribution of this factor to vitiligo vulgaris.ObjectiveTo determine the hypothesized role of migration inhibitory factor in vitiligo via estimation of ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
(24 reference statements)
2
16
0
Order By: Relevance
“…MIF is a proinflammatory cytokine with a role not fully understood in vitiligo; however, it is known that its deletion or neutralization severely impairs the pro-inflammatory cytokine production, such as TNF-α, IL-1β, IL-6, IL-23, and IL-17, [17,18,43] all of which are important in the pathogenesis of vitiligo. In the present study, we observed that MIF serum levels were higher in patients with vitiligo than in CS, in agreement with the only three reports, to our knowledge, published to date on this issue [44][45][46]. However, unlike these authors, we did not find statistically significant differences in our population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…MIF is a proinflammatory cytokine with a role not fully understood in vitiligo; however, it is known that its deletion or neutralization severely impairs the pro-inflammatory cytokine production, such as TNF-α, IL-1β, IL-6, IL-23, and IL-17, [17,18,43] all of which are important in the pathogenesis of vitiligo. In the present study, we observed that MIF serum levels were higher in patients with vitiligo than in CS, in agreement with the only three reports, to our knowledge, published to date on this issue [44][45][46]. However, unlike these authors, we did not find statistically significant differences in our population.…”
Section: Discussionsupporting
confidence: 91%
“…Farag works, [44,46] but not by Serarslan [45] Regarding this, the pleiotropic immunologic and endocrine activities exerted by MIF suggest that its actions may be connected with complex signal transduction pathways. MIF has been associated with the pathogenesis of several chronic diseases, such as rheumatoid arthritis, [47] colitis, [48] types 1 and 2 Diabetes Mellitus, [49] chronic respiratory diseases [50,51], and cancer [52,53].…”
Section: Discussionmentioning
confidence: 94%
“…The contribution of inflammatory DCs (CD11c + CD11b + ) has been demonstrated in DAMP-induced animal model of vitiligo driven by HSP70 (21), however their role in human disease remains to be proven. Studies dating over 10 years ago have demonstrated a positive correlation between levels of macrophage migration inhibitory factor (MIF) in the blood of vitiligo patients and their disease duration suggesting MIF may be a useful serum biomarker of vitiligo activity (38)(39)(40), however direct contribution of macrophages to the disease in the skin is unknown.…”
Section: Role Of Innate Immune Cells In Vitiligomentioning
confidence: 99%
“…MIF is a pro-inflammatory cytokine that has been connected to the development of vitiligo [4]. It has been shown to play a role in a number of immunological and autoimmune diseases.…”
Section: Mif Asavitiligo Incriminating Agentmentioning
confidence: 99%
“…The innate immune response and subsequently, adaptive immunity are triggered by inherent abnormalities in melanocytes and keratinocytes which induce the immunopathogenesis of vitiligo [1]. The proinflammatory cytokine Macrophage migration inhibitory factor has recently been linked to an increased incidence of vitiligo (MIF) [4]. It has been shown to play a role in a number of immunological and autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%